2020
DOI: 10.1037/lhb0000416
|View full text |Cite
|
Sign up to set email alerts
|

Child eyewitness researchers often bin age: Prevalence of the practice and recommendations for analyzing developmental trends.

Abstract: Objective: Effective practices for eliciting and analyzing children's eyewitness reports rely on accurate conclusions about age differences in how children retain information and respond to memory probes. Binning, which is the practice of categorizing continuous variables into discrete groups, can lower studies' power to detect age differences and, in some situations, produce significant but spurious effects. In this article, we (a) describe a systematic review that estimated the frequency of binning age in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Upon ensuring there were no diagnostic differences in brain‐behavior relationships, we further examined BMI and behavior interactions utilizing a dimensional approach. A dimensional approach was chosen because dichotomizing data decreases power while also inflating Type I error rates (Bainter et al, 2020; MacCallum et al, 2002). Additionally, previous work has shown that although children with ASD are more likely to have impaired social and executive functioning, grouping based on executive function did not reproduce diagnostic groups (Baez et al, 2020; Dajani et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Upon ensuring there were no diagnostic differences in brain‐behavior relationships, we further examined BMI and behavior interactions utilizing a dimensional approach. A dimensional approach was chosen because dichotomizing data decreases power while also inflating Type I error rates (Bainter et al, 2020; MacCallum et al, 2002). Additionally, previous work has shown that although children with ASD are more likely to have impaired social and executive functioning, grouping based on executive function did not reproduce diagnostic groups (Baez et al, 2020; Dajani et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Following from research demonstrating that the act of 'binning' ages can cause a loss of power for detecting an effect (Bainter et al, 2020)…”
Section: Suggestibility As a Function Of Agementioning
confidence: 99%
“…Analysis included prior work by the authors into the GME in face-to-face interviews using the same methodology and misinformation paradigm to ensure appropriate and reliable comparisons could be made. Age was analysed continuously to avoid the act of 'binning' participants which can create a lack of power when detecting effects (Bainter et al, 2020). was anticipated that even subtle gestures would have a strong misleading in uence but that this would be less than salient gestures due to stronger visual cues engaging the mirror-neuron system (Proverbio & Zani, 2022) and motor system (Ianì & Bucciarelli, 2017) more robustly.…”
Section: Introductionmentioning
confidence: 99%